Uncovering the Representation of Indonesian Culture: An Analysis of Marjan Syrup Advertisement - Sihombing, Lambok Hermanto (Universitas Muhammadiyah Malang, 2023)
The efforts to preserve the culture could be done in various ways. Advertisement is one of them. This study aims to analyze the advertisement of Marjan syrup, one of the popular Indonesian syrups that not only attempts to attract customers but also introduce Indonesian culture. To examine how Marjan syrup represents Indonesian culture, the object of the study was taken from @Iklanesia HD YouTube channel entitled “Iklan Sirup Marjan-Tari Betawi dan Sepatu Roda”. The author applies a qualitative approach by finding the dataset through literary works. The author utilizes the concept of Advertisement Kia Brandt and Representation from Stuart Hall to analyze how the Marjan syrup advertisement attempts to represent Indonesian culture especially Betawi culture. The findings show that there are several signs of Betawi culture shown in this advertisement. The representation of Betawi culture could be seen through the existence of Ondel-ondel, trumpet, coconut flower (kembang kelape), and mask dance (tari topeng) in the ads. Upaya melestarikan budaya dapat dilakukan dengan berbagai cara. Iklan merupakan salah satu media untuk memperkenalkan budaya. Penelitian ini bertujuan untuk menganalisis iklan sirup Marjan, salah satu sirup populer Indonesia yang tidak hanya berupaya menarik pelanggan tetapi juga memperkenalkan budaya Indonesia. Untuk mengkaji bagaimana sirup Marjan mewakili budaya Indonesia, objek penelitian diambil dari @Iklanesia HD yang berjudul “Iklan Sirup Marjan-Tari Betawi dan Sepatu Roda”. Penulis menerapkan pendekatan kualitatif dengan memperoleh data melalui artikel ilmiah. Penulis menggunakan konsep Advertisement dari Kia Brandt and Representation dari Stuart Hall untuk menganalisis bagaimana iklan sirup Marjan berupaya merepresentasikan budaya Indonesia khususnya budaya Betawi. Hasil dari penulisan artikel ilmiah ini ditunjukkan melalui beberapa simbol dari budaya Betawi. Representasi budaya Betawi adalah Ondel-ondel, terompet, kembang kelapa, dan tari topeng (tari topeng).